Antibacterial Activity and Drug Loading of Moxifloxacin-Loaded Poly(Vinyl Alcohol)/Chitosan Electrospun Nanofibers - Liu, Qi; Ouyang, Wen-Chong; Zhou, Xiu-Hong; Jin, Tao; Wu, Zheng-Wei (Frontiers in Materials, 2021)
In this study, nanofibers with different ratios of poly(vinyl alcohol) and chitosan incorporated with moxifloxacin hydrochloride (MH/PVA/CS) were fabricated through the blending electrospinning, and the morphological features were tested using scanning electron microscopy (SEM). Further characterization of the new nanofiber was accomplished by Thermogravimetric analysis (TG), X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). Antibacterial activity of the MH-loaded nanofibers at different drug loading were tested and compared with the blank group. Experimental results show that the MH/PVA/CS nanofibers exhibited the good antibacterial properties against Staphylococcus aureus and Pseudomonas aeruginosa due to the MH incorporation. Compared with blank nanofibers, MH/PVA/CS nanofibers have significantly better antibacterial properties, and different proportions of PVA and CS have a certain effect on the antibacterial activity of nanofibers. The conclusions in this paper show that MH/PVA/CS composite nanofibers may have great potential in antibacterial materials.